The effects of intermittent fasting diet alone or in combination with probiotic supplementation in comparison with calorie-restricted diet on metabolic and hormonal profile in patients with polycystic ovary syndrome: study protocol for a randomized clinical trial - Sepide Talebi; Sakineh Shab-Bidar; Hamed Mohammadi; Ashraf Moini; Kurosh Djafarian (Trials, 2023)
Abstract Introduction Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in females characterized by ovulatory dysfunction, hyperandrogenism, and other metabolic disorders. Both intermittent fasting and specific probiotics have been suggested to help improve patients with PCOS through changes in gut microbial composition, circadian clock, and metabolic regulation. Therefore, the present study aims to investigate the effects of intermittent fasting alone or in combination with probiotic supplementation compared to the calorie-restricted (CR) diet on anthropometric measures, metabolic status, inflammation, and oxidative stress in women with PCOS. Methods We will carry out a randomized clinical trial for 8 weeks. Participants will be randomly assigned (1:1:1) to one of the three groups: (1) a 14:10 early time-restricted feeding (TRF) diet with probiotic supplementation (n = 30); (2) a 14:10 early TRF diet with placebo supplementation (n = 30); (3) a CR diet (energy-restricted 25% of required calories) with placebo supplementation as a control group (n = 30). The primary outcomes will be changes in body weight and insulin resistance. However, glycemic control, lipid profile, metabolic parameters, sex hormone-binding globulin, dehydroepiandrosterone, anti-Mullerian hormone, free androgen index, hirsutism, acne, antioxidant and oxidant status, inflammation, anthropometric measures, mental health, sleep quality, appetite, eating behavior, food craving, and blood pressure are secondary outcomes. All outcomes of this study will be evaluated in pre- and post-intervention. Discussion We hypothesized that 10-h TRE administered alone or in combination with probiotic supplementation to overweight and obese PCOS subjects would lead to weight loss and improved metabolic, hormonal, inflammatory, and antioxidant markers compared to control subjects following a standard 3-meal-per-day CR diet. Ethical aspects The current trial received approval from the Medical Ethics Committee of Tehran University of Medical Sciences, Tehran, Iran (IR.TUMS.MEDICNE.REC.1401.425). Trial registration Iranian Registry of Clinical Trials IRCT20121110011421N5. Registered on 3 October 2022.